Los cuatro libros de la arquitectura - Palladio, Andrea, 1508-1580 (Fuentes de arte, 2008)
Renaissance architect Palladio was one of the most influential figures the field of architecture has ever produced. Of even greater significance than his buildings is this treatise, one of the most important books in the literature of architecture.